The Types of Support That Enhance Body Image in Patients with Breast Cancer: A Scoping Review - Christaputri, Silvia Tri Wahyu; Triyanto, Arifin; Tsauroh, Salsabila Fiqrotu; Mulyainuningsih, Wa Ode Saridewi; Effendy, Christantie (Journal of Health and Nutrition Research, 2025)
Patients with breast cancer often experience dissatisfaction with themselves as a result of the treatment process they undergo, potentially resulting in a negative body image and affecting the effectiveness of treatment and their quality of life. Therefore, support is needed to address this issue. This study aims to identify the types of support that can be provided to improve body image in patients with breast cancer through a scoping review. We conducted a search using five databases, including ScienceDirect, Wiley, Scopus, ClinicalKey, and ProQuest. The inclusion criteria used were English-language articles and original research articles published between January 2020 and May 2025. Review articles, books, and pilot studies were excluded. The screening procedure was conducted in accordance with the PRISMA 2020 guidelines, and article eligibility was assessed by three researchers using the JBI Critical Appraisal Checklist (2020). Ten articles were obtained, indicating that various forms of support can be provided, such as social support (from family, friends, prominent figures, important or special people, and health workers); partner support; psychological support carried out through clinical interventions; and support from groups of fellow breast cancer survivors, but social support from family being the most commonly implemented form. This support helps patients in the process of improving body image that has changed due to the treatment process; however, in practice, the provision of a single type of support cannot stand alone. These findings affirm that providing support to enhance a positive body image in patients requires thorough attention. Further research is expected to explore the effectiveness of each type of support and involve more than one form of support to produce more comprehensive findings.